Development and validation of a delirium care critical‐thinking scale for intensive care unit nurses: A mixed‐method study - Chang, Yu‐Ling; Hsieh, Ming‐Ju; Pan, Ching‐I; Shang, Shu‐Ting; Tsai, Yun‐Fang (Journal of clinical nursing, 2024)
Aim and Objectives To develop a Delirium Care Critical‐Thinking Scale for nurses caring for patients in the intensive care unit and examine the scale's psychometric properties. Background There is a tool to evaluate nurses' critical thinking skills to determine nursing competency when delirium care is required. Design This cross‐sectional, mixed‐methods study. Methods The Delphi method was applied for collection and analysis of data during conceptualization and item generation of the tool (Phase I). Item analysis, assessment of validity and reliability of the scale (Phase II) involved 318 nurses recruited by convenience sampling from nine adult intensive care units in medicine and surgery at one medical centre. Confirmatory factor analysis assessed construct validity. Internal consistency and 2‐week test–retest stability measured reliability. A Critical Thinking Disposition Inventory Scale examined concurrent validity. Results After three rounds, the Delphi method resulted in 31 scale items. Item analysis demonstrated construct reliability ranged from 9.23 to 16.18. Confirmatory factor analysis eliminated one item and extracted five factors: applying knowledge, confirming the problem and accuracy of information, reasoning logically, choosing appropriate strategies and remaining open‐minded. Average variance extracted values of all factors indicated good convergent validity. Cronbach's α for internal consistency was .96 with good test‐retest reliability. The correlation coefficient for concurrent validity was .301. Conclusion The new Delirium Care Critical‐Thinking Scale for intensive care nurses was demonstrated to be a reliable and valid tool for evaluating their ability to assess patients with delirium. Relevance to Clinical Practice This new scale could be used to assess outcomes of education interventions and the effectiveness of nursing care quality involving patients with delirium in intensive and critical care units. Reporting Method The COSMIN checklist was used as the reporting guideline for this study. Patient or Public Contribution None.